Meal-exercise challenge and physical activity reduction impact on immunity and inflammation (MERIIT trial) - Silva, Diana (2019)
The effect of a pre-exercise meal as countermeasure to exercise induced immunodepression is poorly known. Also, sedentary behavior is associated with increased cardiometabolic risk but studies on immune changes are lacking. Therefore, we aimed to assess: 1) the impact of a pre-exercise Mediterranean meal (MdM) compared with a fast-food type meal (FFM) on exercise-induced immunological changes and 2) the impact of an induced acute period of sedentary behavior on neuro-immune-endocrine status.